Escolarização de alunos com altas habilidades/superdotação: um apoio virtual - Francisco, Priscyla Ramos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
According to current legislation, is part of the Target of Special Education, students with high abilities/giftedness (HA/G). However, it appears that there are few studies on efficiency and effectiveness of diverse pedagogical practice for students with these characteristics. With increasing globalization, are multiplied opportunities for transnational education programs and educational services, particularly through the Internet, increasing the need for information services and accreditation of institutions and educational programs. This study aims to: a) develop a website containing information on high abilities/giftedness; b) evaluate the design of teachers on applicability of the site; c) analyze the contributions posted on the site. Therefore, it was available to the participants of this research produced site. Consisted on the site, among other information, those relating to HA/G indicators. Was sent a questionnaire via the Internet, with nine closed questions and two open, to 2000 teachers, registered in the database Improvement Course in Educational Practices Inclusive conducted by UNESP, under the coordination of Prof. Dr. Vera Lucia Messias Fialho Capellini. Data were considering frequency responses. For the treatment we used the Google Docs. As result Program Observed how teachers are lacking this subject deserves further Top depth. Concerning the site he was Considered by the participants as a support tool to the teacher, Which helps to identify and recognition of Individuals with HA/G and contributes to information, training and practical pedagogical way. This, is expected to Contribute to the dissemination of this issue in society as well as the Possibility of Minimizing the myths about this population, since such myths exist due to the lack of information

De acordo com a legislação vigente, faz parte do público alvo da educação especial, alunos com altas habilidades/superdotação (AH/SD). No entanto, constata-se que são poucos os estudos que abordam eficiência e efetividade de prática pedagógica diversificada para estudantes com essas características. Com o crescimento da globalização, encontram-se multiplicadas as oportunidades para a oferta transnacional de programas e serviços de ensino, particularmente por meio da internet, aumentando a necessidade de serviços de informação e credenciamento de instituições e programas educacionais. Assim, este estudo tem como objetivos: a) desenvolver um site contendo informações sobre altas habilidades/superdotação; b) avaliar a concepção dos professores sobre aplicabilidade do site; c) analisar as contribuições postadas no site. Para tanto, foi disponibilizado aos participantes desta pesquisa o site produzido. Constaram no site, entre outras informações, as que se referem aos indicadores de AH/SD. Foi enviado via internet um questionário, com nove questões fechadas e duas abertas, a 2000 professores, cadastrados no banco de dados do Curso de Aperfeiçoamento em Práticas Educacionais Inclusivas, realizado pela UNESP, sob a coordenação da Prof. Vera Lúcia Messias Fialho Capellini. Os dados foram tratados considerando frequência de respostas. Para o tratamento foi empregado o Programa Google Docs. Como resultado observou quão carente os professores são desta temática que precisa ser mais aprofundada. Concernente ao site ele foi considerado pelos participantes como uma ferramenta de apoio ao professor, que auxilia na identificação e reconhecimento de indivíduos com AH/SD e contribui para a informação, formação e prática pedagógica. Desta forma, espera-se contribuir para a disseminação desta temática na sociedade, bem como na possibilidade de minimizar os mitos em relação a esta população, já que tais mitos..
Keywords: Educação especial; Superdotados; Tecnologia; Internet; Avaliação educacional; Special education